2023
DOI: 10.1136/bmjopen-2022-066367
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the COVID-19 pandemic and social media on the behaviour of pregnant and lactating women towards vaccination: a scoping review

Abstract: BackgroundPregnant women, foetuses and infants are at risk of infectious disease-related complications. Maternal vaccination is a strategy developed to better protect pregnant women and their offspring against infectious disease-related morbidity and mortality. Vaccines against influenza, pertussis and recently also COVID-19 are widely recommended for pregnant women. Yet, there is still a significant amount of hesitation towards maternal vaccination policies. Furthermore, contradictory messages circulating soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Such concerns are not unheard of and have been previously reported. De Brabandere et al ( 29 ) showed in their systematic review that safety concern, among pregnant women, was the most important factor driving vaccine hesitancy, as was in Saudi Arabia too ( 19 ). Temsah and colleagues also reported the concern of long-term effect of the vaccine as a driver of vaccine hesitancy in Saudi Arabia ( 28 ), while the work of Aldossari et al ( 30 ) highlighted the concern of genetic abnormalities as a result of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Such concerns are not unheard of and have been previously reported. De Brabandere et al ( 29 ) showed in their systematic review that safety concern, among pregnant women, was the most important factor driving vaccine hesitancy, as was in Saudi Arabia too ( 19 ). Temsah and colleagues also reported the concern of long-term effect of the vaccine as a driver of vaccine hesitancy in Saudi Arabia ( 28 ), while the work of Aldossari et al ( 30 ) highlighted the concern of genetic abnormalities as a result of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…[8]. According to the scoping review by De Brabandere et al, maternal vaccination heavily relies on the internet and social media as important sources of information [9]. Meanwhile, medical and administrative professionals, including gynaecologists and obstetricians, have continued their efforts to disseminate information to the general public, who are not medical professionals, via society websites and other means in order to communicate accurate information to pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that "media" can influence the anxiety of pregnant women about COVID-19 and their vaccination behaviour [9], it is unclear how pregnant women with specific backgrounds select which media to obtain information about COVID-19 and vaccination. Although it has already been reported that COVID-19 vaccination during pregnancy can suppress severe symptoms in pregnant women who have been infected with SARS-CoV-2 [10,11], there are a certain number of pregnant women who have not received the vaccine due to vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic taught us that maternal vaccine hesitancy might be countered with additional efforts to reduce parental anxiety and increase vaccination adherence rates. Attempts should include a revised communication strategy based on ad hoc intervention and simplified language, spread by social media or video conferencing apps for webinars, via one-on-one counseling, or in small groups with the opportunity to receive vaccination contextually. Our experience in Milan, Italy, was characterized by monthly webinars, open chat to ask and obtain answers regarding concerns about safety, efficacy, and the rapid development and approval of the COVID-19 vaccine, as well as the opportunity to obtain the vaccines .…”
mentioning
confidence: 99%